Pelan pengurusan keselamatan dan kesihatan pekerjaan di tempat kerja bagi bangunan tinggi - Othman, Mohd. Radzlee (2007)
This research aims to identify and measure the implementation of Occupational Safety and Health Management Plan at Menara SME Bank. This research also identifies the involvement and responsibility of the management and employees as said in the Act 514. The first objective is to identify and measure the knowledge and awareness of the OSH management plan in work place especially within the SME’s Bank staff in the building. Second objective is to identify the achievement of implementation of the OSH management plan that involves the commitment from the management and employees participation. Descriptive analysis, frequency analysis, crosstabs analysis and also correlation analysis are applied to analyze the factor and measurement for OSH management plan that have been practice. From literature review, there are five basic element involve in a successful health and safety management plan. Five elements are; policy, organizing, planning and implementation, evaluation and action for improvement. This main element evolves from the concept of continual improvement in all activities and accident prevention. The result of analysis shows that management high commitment and participation is the main factor to make the OSH management plan successfully and to achieve the plan objective. Therefore the senior management especially the President must seriously take part with this exercise. With strong commitment from the management and employee participation, it is the organization hope to achieve the Malaysian Standard award MS1722:2005 OSH Management System and subsequently developing health and safe working culture.